Pengaruh Employee Engagement terhadap Turnover Intention di Perusahaan Katering - Amrina Rohayyan; Bambang Wardoyo; Muhammad Eko Abrian Kusuma (Jurnal Pengembangan Ketenagakerjaan, 2025)
Organizations must strive to improve employee engagement in the organization in order to increase employee engagement and loyalty. The purpose of this study was to analyze how employee engagement affects turnover intention at Catering Company and to analyze how much influence employee engagement has on turnover intention at Catering Company. Data collection in this study was done by distributing questionnaires to 87 Head Office employees at Catering Company which were obtained from the solvin formula and proportionate stratified random sampling technique. The data collected were processed using simple linear regression analysis using the SPSS 22 application. The results of this study indicate that there is a negative and significant effect between employee engagement and turnover intention with value of -0.557. So the higher the employee engagement, the lower the turnover intention, so the company needs to conduct an employee engagement survey to determine the level of employee engagement at Catering Company. In addition, companies need tFo make efforts to increase employee engagement by readjusting the workload of employees as an effort to reduce boredom and work stress experienced by employees. Companies also need to reduce turnover intention by reviewing the size of the wage scale structure.